Fabrication of Sulfasalazine-Loaded Solid Lipid Nanoparticles through Solvent Emulsification Diffusion Technique: Pharmaceutical and Stability Studies - Maqsood ur Rehman; Aziz ur Rahman; Islam, Zahoor; Khan, Numan; Nazir, Ayesha; Saeed, Akif (Indus Journal of Bioscience Research, 2025)
Background: Sulfasalazine (SSZ), a Biopharmaceutical Classification System (BCS) Class IV drug, suffers from poor aqueous solubility and low bioavailability, limiting its therapeutic efficacy. Solid lipid nanoparticles (SLNs) offer a promising nanotechnology-based approach to improve solubility, stability, and controlled drug release. Objective: To formulate and optimize sulfasalazine-loaded SLNs using the solvent emulsification diffusion technique, evaluate their physicochemical properties, and assess their potential for sustained drug release. Methods: Unloaded SLNs were prepared by varying lipid (stearic acid), surfactant (Tween-80), co-surfactant (PEG-400) concentrations, and stirring times. The optimized formulation (BFM-11) was used to load SSZ at various drug-to-lipid ratios. Zeta size, polydispersity index (PDI), zeta potential, entrapment efficiency (EE), drug-loading capacity (DLC), and in vitro release profiles were assessed. Stability studies were conducted at 5±3°C and 25±2°C for 30 days. Results: The optimized formulation (SFM-3) achieved a zeta size of 217.2 nm, PDI of 0.373, zeta potential of -38.72 mV, EE of 89.1%, and DLC of 2.87%. In vitro release demonstrated 21.46% release in the first hour with 92.31% cumulative release over 12 hours. Stability was maintained at 5±3°C but deteriorated at 25±2°C. Conclusion: Sulfasalazine-loaded SLNs improved drug solubility, stability, and sustained release, presenting a promising nanotechnology-based strategy for enhancing therapeutic efficacy.